NILAI ESTETIS DAN â€œDULCE ET UTILEâ€ DALAM NOVEL KEINDAHAN DAN KESEDIHAN KARYA KAWABATA YASUNARI - Novi Andari (Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. This article is exploring the aesthetical aspects of Yasunariâ€™s novel Keindahan dan Kesedihan. Â Aesthetic aspects applied here are in accordance with those of Horace, that is dulce et utile. Through analyzing these aspects, one may come to the judgment whether a literary work is a great work or not.Â The result of analysis shows that Yasunariâ€™s Keindahan dan Kesedihan applies a good quality of dulce et utile. It can be sense in the existence of the unity in variety, disinterested contemplation, aesthetic distance, framing, invention, and creation and one may read the use of selected dictions and may gain values from reading the novel.Â Key words : aesthetic value, dulce et utile, Â aesthetic distance, framing